Determination of sialic acid and biochemical parameters level in β-thalassemic patients - Muna Khalil Murtadha (College of Pharmacy / Mustansiriyah University, 2011)
This research was concerned with the biochemical changes that might occur in patients with β-thalassemia major, multiple determinations were obtained 20 subjects: - 13 children with β-thalassemia major and 7 normal children (as normal healthy control). The parameters deduced from this study includes:- serum total sialic acid (TSA), erythrocytes sedimentation rate (ESR) and seromucoid total protein (TP). From the data obtained for these parameters investigate the decrease in serumTSA and TP of thalassemic patients compared to normal individuals, while the ESR levels increase for patients as compared to other individuals.